Detection of Theileria equi‎ in Baghdad Racing Horses Using ‎Hematological and ‎Molecular Assay - N ALani, Ahmed; A Yousif, Afaf (The Iraqi Journal of Veterinary Medicine, 2023)
The aim of this study was to investigate the prevalence of Theileria equi‎ infection in racing ‎horses in ‎‎Baghdad governorate, utilizing clinical signs, microscopic examination, molecular ‎assays, and ‎hematological ‎tests to identify significant differences between infected and non-‎infected horses. Between ‎January and ‎December 2021, a total of 160 racing horses from three ‎locations in Baghdad governorate (Al-‎Amiriya ‎Equestrian Club, Arabian horses in Alzwraa ‎Zoo, and Iraqi Equestrian School) were randomly ‎selected for ‎examination. Microscopic ‎examination of blood smears revealed 11 positive samples for ‎Theileria equi‎ ‎‎(6.875%), while ‎the results of the polymerase chain reaction assay targeting the 18S ‎ribosomal RNA gene ‎‎confirmed 26 positives (16.25%). Sequenced amplicons and phylogenetic tree analysis ‎‎revealed a genetic ‎similarity of 93.03–‎100% and 94-100% site coverage compared to many ‎global ‎countries’ isolates. ‎Interestingly, only 16 (61.5%) of the 26 infected horses showed ‎mild to subclinical ‎symptoms or were ‎carriers of the disease without tick infestation. ‎Hematological blood parameters ‎showed non-significant ‎differences between infected and ‎non-infected horses, except for a decrease in ‎packed cell volume (PCV) ‎and hemoglobin (Hb) ‎concentration, which caused anemia in 12 horses among ‎the 26 molecularly positive ‎cases ‎‎(46.15%). Of these cases, 6 horses (23.08%) had normocytic ‎normochromic anemia, while 3 ‎‎(11.54%) ‎cases each had normocytic hypochromic and microcytic ‎hypochromic anemia. ‎Notably, young horses (two ‎years old) were more susceptible to infection (odds ratio ‎‎15.4) ‎than those over six years old. Additionally, ‎sex and breed did not show any significant ‎correlation ‎with equine theileriosis. In conclusion, this study ‎detected Theileria equi‎ infection ‎in young racing horses in ‎Baghdad. Clinically, most infected cases showed ‎mild to ‎asymptomatic signs accompanied by anemia. ‎Molecular investigation revealed high genetic ‎‎similarity to isolates reported globally. These findings ‎highlight the importance of ‎implementing measures ‎to control and prevent the spread of Theileria equi‎ in ‎racing horses in ‎Baghdad and other regions. Further ‎studies are warranted to better understand the ‎‎epidemiology, pathogenesis, and risk factors associated ‎with equine theileriosis‎.